Brief report: Characterization of electronic cigarette use among patients of a comprehensive cancer center - Robinson, Jason D.; Kypriotakis, George; Karam‐Hage, Maher; Cui, Yong; Beneventi, Diane; Blalock, Janice A.; Minnix, Jennifer A.; Cinciripini, Paul M. (The American journal on addictions, 2024)
Background and Objectives We provide an initial characterization of e‐cigarette use among adult cancer patients. Methods Data were collected between November 2020 and August 2022 at a comprehensive cancer center. Results Relatively few (4.59%) of the assessed patients (n = 47,117) reported ever using e‐cigarettes. Over one‐third of current e‐cigarette users reported being current combustible cigarette users. Discussion and Conclusions These data suggest that e‐cigarette use is uncommon but associated with other tobacco use among adult cancer patients. Scientific Significance This is among the first comprehensive surveys of adult cancer patient e‐cigarette use that details the types of e‐cigarette and other tobacco products used by this population.